The World Isn’t Fair, but Shouldn’t Elections Be? Evaluating Prospective Beliefs about the Fairness of Elections and Referenda - Jonathan Rose; Cees van der Eijk (Societies, 2022)
Almost all academic literature about the causes and consequences of fairness of elections and referenda is based on retrospective evaluations. One of the strongest findings of such studies is that nonvoting is higher among citizens who retrospectively perceived an election as unfair. However, on logical grounds, it is impossible to attribute lower rates of voting to retrospectively perceived unfairness because at the time of the vote citizens can only rely on their prospective expectations of fairness. Moreover, it is well documented that retrospective evaluations are strongly influenced by the outcome of the election which is, at the time of voting, still unknown. In view of the dearth of earlier studies on prospective views of electoral fairness, this article presents the first major exploratory analyses of determinants and consequences of prospective expectations of electoral fairness. Using data from Britain about expectations of fairness of three general elections and two referenda in the period between 2014 and 2019, it shows that the public hold mixed views about the fairness they expect to find when voting. The article demonstrates that these prospective fairness beliefs are sometimes noticeably different to retrospective beliefs in terms of their predictors. Moreover, in sharp contrast to literature based on retrospective evaluations, this article also finds that prospective evaluations do not importantly affect the decision to vote. These findings have important implications for how we understand and evaluate the inclusiveness of elections.